2013
DOI: 10.3390/v5041131
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of a Novel Recombinant Antibody against LMP1-TES1 of Epstein-Barr Virus Isolated by Phage Display

Abstract: Latent Membrane Protein 1 (LMP1) is a primary target for controlling tumorigenesis in Epstein-Barr virus related malignancies; in this study, we aimed to develop a specific antibody against the TES1 domain of the oncogenic LMP1. We screened a full human naïve Fab phage library against TES1 peptide, which consisted of C terminal-activating regions proximal 44 amino acids. After three rounds of panning, enrichment and testing by phage ELISA and further analyzed by DNA sequencing, we selected a phage clone with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…A few studies have suggested several molecular biomarkers of ovarian cancer 26 27 . In our previous research, we have identified several oncogenic biomarkers, constructed related human monoclonal antibody-based drugs and tested their anti-tumor effectiveness 28 29 30 31 . Similarly, we have been searching a novel and valuable marker which associates with ovarian cancer and could be used as a potential candidate for targeted therapy with monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have suggested several molecular biomarkers of ovarian cancer 26 27 . In our previous research, we have identified several oncogenic biomarkers, constructed related human monoclonal antibody-based drugs and tested their anti-tumor effectiveness 28 29 30 31 . Similarly, we have been searching a novel and valuable marker which associates with ovarian cancer and could be used as a potential candidate for targeted therapy with monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…71 To date, the isolated EBV mAbs mainly target the viral envelope proteins or the viral latent proteins. [72][73][74][75][76][77] Generally, antibodies against the viral envelope proteins interfere the viral entry process, which is known as neutralization, and antibodies targeting viral latent proteins may exert cytotoxic functions. 71,78 Here, we summarized the antiviral potency or complement receptor type2 (CR2), 79 and followingly gp42 binds human leukocyte antigen (HLA) class II to trigger gB conformational change for membrane fusion and viral entry.…”
Section: Ebv Antibodies As Antiviral Agents For Infection and Its Ass...mentioning
confidence: 99%
“…To date, the isolated EBV mAbs mainly target the viral envelope proteins or the viral latent proteins 72–77 . Generally, antibodies against the viral envelope proteins interfere the viral entry process, which is known as neutralization, and antibodies targeting viral latent proteins may exert cytotoxic functions 71,78 .…”
Section: Ebv Antibodies As Antiviral Agents For Infection and Its Ass...mentioning
confidence: 99%
“…Identification of LMP1 expression is drawing attention as a favorable target for ENKTL treatment [ 11 , 12 ]. In our previous researches, we have reported the prognostic characteristics of LMP1 in lymphoma and have generated an anti-LMP1 Fab antibody (LMP1-Fab), exerting potential anti-tumor activity in nasopharyngeal carcinoma (NPC) [ 13 18 ]. Because of the remarkable relationships between LMP1 expression and ENKTL properties, an anti-LMP1 antibody should bring positive consequences in ENKTL treatment.…”
Section: Introductionmentioning
confidence: 99%